Transtheoretical-Based Model of Intervention for Diabetes and Prediabetes: A Scoping Review - Daniel Miezah; Mustapha Amoadu; Priscilla Nyamekye Opoku; Enoch Mensah Junior; Jethro Zutah; Paul Obeng; Jacob Owusu Sarfo (Journal of Diabetes Research)
Diabetes is considered a public health problem worldwide, fostered by population growth, an increase in the overall quality of life, changes in dietary patterns, modifications in lifestyle habits, and the natural process of getting older. To properly control diabetes, the transtheoretical model (TTM) may be useful. This scoping review is aimed at identifying TTM interventions for diabetes. The study followed Arksey and O’Malley’s six steps in conducting the scoping review. Four main databases (PubMed, Central, JSTOR, and ScienceDirect), Google Scholar, Google, and a reference list of identified articles were searched for literature. The study included peer-reviewed articles published online from 2000 to 2023 and published in the English language. At the end of the search, 3,514 entries were found in the four main databases, and 23 records were identified through Google, Google Scholar searches, and reference lists. After a thorough screening, 22 records were used for this review. The study found that the primary interventions based on the TTM for managing diabetes and prediabetes were educational materials to promote physical activity among diabetes and prediabetes individuals, health education, exercise, motivational interviews, self-tracking, and dietary changes. Further interventions on diabetes and prediabetes management could adopt the identified transtheoretical interventions to improve the health of their patients.